Herding Behavior and Its Impact on Purchasing Decisions Among Beginner Crypto Investors: An Experimental Analysis - Wijaya, Yohanes Hendy; Elgeka, Honey Wahyuni Sugiharto (Gadjah Mada Journal of Psychology (GamaJoP), 2024)
In recent years, cryptocurrency has garnered significant interest from investors. Herding behavior bias frequently influences the rationality of purchasing decisions in novice crypto investors. In addition, greed can affect the decision-making process regarding the nominal of investment. This study aimed to examine the role of herding behavior in novice crypto investors' purchasing decisions and assess the role of greed as a moderator. The study employed an experimental method with a posttest-only control group design. Thirty participants were selected using convenience sampling techniques and divided into two groups (experiment and control groups). Data analysis was conducted using the Mann-Whitney U test for comparison testing and PROCESS Hayes for moderation analysis. The results indicated that herding behavior played a significant role in purchasing decision-making (U = 60; p < 0.05), whereas greed did not serve as a moderator in the relationship between herding behavior and nominal decision-making (b = -0.001; CI = -0.075, 0.072; p > 0.05). Instead of relying on rational decision-making, novice cryptocurrency investors frequently succumb to herding behavior. The ambiguity of information and investors' inability to make informed decisions lead to herding behavior being perceived as the most viable option.